Homebound Elderly People Psychotherapeutic Intervention (HEPPI): study protocol for a randomized controlled trial - Andreia Gabriel Jesus; Margarida Pedroso de Lima; Manuela Vilar; Nancy Ann Pachana (Brazilian Society of Geriatrics and Gerontology, 2023)
Objective: To present the study protocol for the Homebound Elderly People Psychotherapeutic Intervention (HEPPI), a home-delivered cognitive-emotional intervention aimed at homebound older adults with mild cognitive impairment and depression and/or anxiety symptoms. Methods: A two-arm, open-label, parallel-group randomized controlled trial will be conducted to compare the effects of HEPPI with treatment as usual. Homebound older adults will be recruited from the community through contact with their health care networks in mainland Portugal. All participants will complete baseline, post-intervention, and 3-month follow-up assessments. Primary outcomes will be changes in episodic memory and depression and anxiety symptoms. Secondary outcomes will include changes in general cognition, attentional control, subjective memory complaints, quality of life, functional status, and loneliness. Relevance: The availability of evidence-based home-delivered non-pharmacological interventions meeting the cognitive and emotional needs of the homebound older population could improve their access to mental health care resources and increase their mental health and quality of life.